Testing the information-based trading hypothesis in the option market: Evidence from share repurchases - Ihsan Ullah Badshah; Hardjo Koerniadi; James W. Kolari (Journal of Risk and Financial Management, 2019)
The informed options trading hypothesis posits that option prices lead stock prices. In this paper, we extended the research on this hypothesis to open-market share repurchases. Empirical tests showed that the implied volatility spread was not significantly related to buy-and-hold abnormal stock returns. However, further evidence reveal a significant relationship between implied volatility spread and subsequent stock return volatility around open-market share repurchase events. We concluded that option traders have private information on the volatility of stock returns and superior information processing ability that accounts for prescient pricing behavior in options relative to stocks.
Keywords: 330; event study; informed trading; options; share repurchase; US equity market; volatility spread